The Effect of Bauhinia bowkeri Extracts on Hypercholesterolemia: Insights from In Vitro and In Silico Investigations - Siphelele T. Thethwayo; Evelyn Madoroba; Sphamandla Masikane; Andrew R. Opoku; Nkosinathi D. Cele (Plants)
Despite the many current cholesterol-lowering drugs on the market, the persistent surge of hypercholesterolemic-related complications ignites a fascinating search for the discovery of novel therapeutics. This study aimed at investigating the anti-hypercholesterolemic effect of Bauhinia bowkeri extracts. The plant material was sequentially extracted with n-hexane, dichloromethane (DCM), and 70% ethanol. The phytochemical constituents of the extracts were analyzed through GC-MS and the antioxidant activity of the extracts was screened against a wide range of free radicals (ABTS, DPPH, hydroxyl radical, and nitric oxide). The extracts were also screened for the metal iron chelating and reducing power potential. The enzyme inhibitory activity of the extracts on pancreatic lipase, cholesterol esterase, and HMG-CoA reductase as well as the bile acid binding capacity were evaluated. Among the total of 122 compounds detected in the three extracts, only 7 compounds (E-15-Heptadecenal, Diethyl Phthalate, 9,12,15-Octadecatrienoic acid ethyl ester, (Z,Z) Tetradecane 5-methyl, and Octadecane 5-methyl) were found to be common in all the extracts. The extract displayed a varying degree of efficiency on free radicals with IC50 values ranging from 0.07 mg/mL to 0.41 mg/mL. A concentration-dependent inhibition of pancreatic lipase and cholesterol esterase activities, along with a reduction in the bile-binding capacity exhibited by the extracts, was noted. In silico investigations of some of the phytoconstituent revealed significant inhibition of HMG-CoA reductase, cyclooxygenase, and hormone-sensitive lipase with a binding affinity that ranged between −5.1 and −7.0 kcal/mol. These findings suggest that Bauhinia bowkeri extracts possess potential antioxidant and anti-hypercholesterolemic properties.